Sex-Dependent Vulnerability to Cannabis Abuse in Adolescence - Rubino, Tiziana; Parolaro, Daniela (Frontiers in Psychiatry, 2015)
The goal of this review is to summarize current evidence for sex differences in the response to cannabinoid compounds, focusing mainly on a specific age of exposure, i.e. adolescence. Preclinical as well as clinical studies are examined. Among the different possible underlying mechanisms, the consistent dimorphism in the endocannabinoid system and THC metabolism may play a part. All the collected data point to the need of including females in basic research as well as of analyzing results for sex differences in epidemiological studies.